Association Between Vulvar Squamous Intraepithelial Lesions and Psychiatric Illness. Issue 1 (January 2021) - Bell, Sarah G.; Kobernik, Emily K.; Haefner, Hope K.; Welch, Kathryn C.
Abstract : Objectives: The aims of the study were to describe and to compare demographics and the prevalence of psychiatric disorders among patients with low- and high-grade vulvar squamous intraepithelial lesions. Methods: A retrospective chart review was performed for patients presenting to a vulvar diseases clinic between 1996 and 2019 ( N = 2, 462). Intake questionnaire data were entered into a deidentified database. Results were compared between 80 patients with biopsy-confirmed high-grade squamous intraepithelial lesions (HSILs) and 48 patients with biopsy-confirmed low-grade squamous intraepithelial lesions (LSILs). Bivariate analysis was performed to compare demographics and psychiatric treatment and outcomes across HSIL and LSIL groups. Results: Among 128 patients with vulvar disease, 80 (62.5%) had HSILs and 48 (37.5%) had LSILs. Patients with HSILs were significantly older (HSIL median [interquartile range] = 49.0 (39.0–61.0) vs LSIL = 36.0 [29.0–53.0], p = .006). There were no significant differences between groups across race/ethnicity, education, marital status, or self-reported household income categories. Forty percent of HSIL patients reported depression compared with 20.8% of LSIL patients ( p = .03), whereas 31.3% of HSIL patients and 8.3% of LSIL patients reported anxiety ( p = .002). Bipolar disorder was reported in 3.8% of HSIL patients and no LSIL patients ( p = .29). There were no differences in the proportion of patients receiving psychiatric counseling, medications, or hospitalizations between groups. Conclusions: Squamous intraepithelial lesions of the vulva are associated with psychiatric disorders above age-matched national averages; these disorders are more prominent in the HSIL group. Combining mental health services with ongoing disease treatment seem to be part of a comprehensive approach to caring for this patient population.